Produção de enzimas hidrolíticas por fermentação em estado sólido e secagem por spray drying - Aita, Bruno Carlesso (2020)
The entomopathogenic fungus Metarhizium anisopliae is used for the biological control of agricultural pests due to the secretion of a complex of hydrolytic enzymes such as chitinase and β-1,3-glucanase. In recent years, much attention has been paid to the use of these enzymes as an active ingredient in bioproducts. Thus, this study was focused on the production of hydrolytic enzymes by solid state fermentation (SSF) and its drying by spray drying. Different substrates (sugarcane bagasse, malt bagasse and white rice) supplemented with corn steep liquor, soybean meal and chitin were evaluated for enzymatic production by SSF with the fungus Metarhizium anisopliae IBCB 348. Sugarcane bagasse was the best substrate for enzymatic production, with activities of 12.07, 11.54, 20.87 and 22.30 U/g for chitinase, β-1,3-glucanase, endocellulase and exocellulase, respectively. The best conditions of SSF for enzymatic production were moisture content of 40%, inoculum concentration of 10% (v/w), temperature of 28 °C and 8 days of fermentation. Evaluating the spray drying process of the enzymatic broth obtained by SSF, the combination of adjuvants maltodextrin (2.5% w/v), arabic gum (2.5% w/v) and soluble starch (5.0% w/v) presented the best results of residual activities of β-1,3-glucanase (88.36%) and chitinase (69.82%), and a powder recovery yield of 45.49%. The operational parameters of the spray drying process were optimized using a Central Composite Rotational Design (CCRD), with the optimum conditions being: drying air inlet temperature of 120 °C, drying air flow rate of 1.1 m³/min, feed flow rate of 5.8 mL/min and atomizer air pressure of 0.4 MPa. The powder produced in the optimized conditions showed 65.6% efficiency in the control of Ceratitis capitata. These results demonstrated the potential of SSF for the production of hydrolytic enzymes and the possibility of its drying by spray drying.